Intestinal Lymphatic Endothelial Cells Produce R-Spondin3 - Reiki Ogasawara (Nature Portfolio, 2018)
Abstract The R-Spondin (R-Spo) family regulates WNT signaling and stimulates the proliferation and differentiation of intestinal stem cells (ISCs). R-Spo plays a critical role in maintaining intestinal homeostasis, but endogenous producers of R-Spo in the intestine remain to be investigated. We found that R-Spo3 was the major R-Spo family member produced in the intestine and it was predominantly produced by CD45−CD90+CD31+ lymphatic endothelial cells (LECs) in the lamina propria of the intestinal mucosa. Transcriptome analysis demonstrated that LECs highly expressed R-Spo receptor, Lgr5, suggesting an autocrine stimulatory loop in LECs. LECs were significantly reduced in number, and their R-Spo3 production was impaired in intestinal graft-versus-host disease (GVHD) after allogeneic hematopoietic stem cell transplantation. The impaired production of R-Spo3 in the intestine may be a novel mechanism of delayed tissue repair and defective mucosal defense in intestinal GVHD. We demonstrate a novel role of intestinal LECs in producing R-Spondin3 to maintain intestinal homeostasis.